FETAL MACERATION IN A DOG - X, SOPHIA; C, JAYAKUMAR; ABHILASH; S, R; J, DEEPAK (The Indian Journal of Animal Reproduction, 2022)
A female dog crossed 61 days back with a history of brownish black vaginal discharge was confirmed of foetal maceration based on radiographic and sonographic findings. Therapeutic management with a combination of mifepristone and misoprostol failed to expel the foetus and a hysterotomy was performed to remove it. The dog had a successful conception in the subsequent estrus.